SOCIAL CHANGE AND COMMUNICATION IN ISLAMIC CONTEXTS: EXPLORING THE ROLE OF FAITH IN ORGANIZATIONAL DEVELOPMENT - Muftitama, Adriansyah; Adam Idris; Omar, Rina Haji (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
The role of faith in organizational development has gained increasing attention, particularly in Islamic contexts where religious principles shape organizational practices and communication strategies. Islamic values such as justice, Shura (consultation), and community welfare have profound implications for organizational behavior, leadership, and social responsibility. This study aims to explore how these faith-based principles influence organizational communication and contribute to social change. The research focuses on Islamic organizations, examining the integration of faith in decision-making, communication practices, and community engagement. A qualitative case study approach was employed, incorporating interviews with organizational leaders and employees, document analysis, and observations across five Islamic organizations. The findings suggest that the incorporation of Islamic values leads to more inclusive decision-making processes, stronger communication channels, and a heightened sense of social responsibility. Organizations that prioritized faith-based values demonstrated greater transparency, employee engagement, and community involvement. The study concludes that faith plays a central role in fostering social change within organizations, enhancing both internal development and broader societal impact. Integrating Islamic values into organizational practices not only promotes ethical decision-making but also drives positive social transformation. These findings contribute to the understanding of faith-based organizational development and offer practical insights for integrating religious values in modern organizational contexts.